The Design Of Engineering Business Process Using Six Sigma Framework PT. Energi Makmur - Hanafi, Muhammad; Pramudito, Adrian (Dinasti International Journal of Digital Business Management, 2024)
The SARS-CoVID-19 pandemic has had a devastating impact on various sectors, prompting countries worldwide to implement measures like social restrictions. PT. Energi Makmur, a national Engineering Procurement and Construction Company, adapted to these changes during the pandemic, facing numerous challenges while striving to deliver products to clients within specified timelines. This final project aims to create a novel business process for the Front End Engineering Design phase that can effectively operate under social restrictions, removing the need for physical coordination typically conducted in an office setting. Using the Design for Six Sigma framework, incorporating Define, Measure, Analyze, Design, and Verify steps, this project seeks to maintain internal approval timelines akin to those in normal conditions. Primary data collection involves interviews, group discussions, and surveys, while secondary data is gathered through internal document review. To identify root causes, methods like the current reality tree and the 8 waste theory are employed, while the FMEA method is utilized to prioritize solutions, and the Kano model verifies the design. Nine proposed solutions emerged from the design phase, with seven slated for implementation in upcoming projects after the verification stage.